2012
DOI: 10.1155/2012/625170
|View full text |Cite
|
Sign up to set email alerts
|

ESBLs: A Clear and Present Danger?

Abstract: Extended spectrum β-lactamases (ESBLs) are enzymes produced by a variety of Gram negative bacteria which confer an increased resistance to commonly used antibiotics. They are a worrying global public health issue as infections caused by such enzyme-producing organisms are associated with a higher morbidity and mortality and greater fiscal burden. Coupled with increasing prevalence rates worldwide and an ever diminishing supply in the antibiotic armamentarium, these enzymes represent a clear and present danger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
147
2
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(162 citation statements)
references
References 90 publications
1
147
2
12
Order By: Relevance
“…Con base en los estudios identificados, en los últimos años (2009 a 2011) la frecuencia de BLEE podría situarse entre 10,1 y 11,8 % en E. coli y entre 14,6 y 32,6 % en K. pneumoniae. A nivel mundial, los datos del estudio TEST (Tigecycline Evaluation and Surveillance Trial) (56)(57)(58)(59), los del proyecto Sentry (60) y los del estudio SMART (Study for Monitoring Antimicrobial Resistance Trends) muestran cómo en la última década las tasas más altas se observan en Asia, seguidas por las de América Latina y, por último, las de los países desarrollados (61)(62)(63). Al comparar la situación de Colombia con los datos reportados, en el caso de K. pneumoniae productora de BLEE el país estaría al nivel de América Latina, con las tasas de resistencia más altas.…”
Section: Discussionunclassified
“…Con base en los estudios identificados, en los últimos años (2009 a 2011) la frecuencia de BLEE podría situarse entre 10,1 y 11,8 % en E. coli y entre 14,6 y 32,6 % en K. pneumoniae. A nivel mundial, los datos del estudio TEST (Tigecycline Evaluation and Surveillance Trial) (56)(57)(58)(59), los del proyecto Sentry (60) y los del estudio SMART (Study for Monitoring Antimicrobial Resistance Trends) muestran cómo en la última década las tasas más altas se observan en Asia, seguidas por las de América Latina y, por último, las de los países desarrollados (61)(62)(63). Al comparar la situación de Colombia con los datos reportados, en el caso de K. pneumoniae productora de BLEE el país estaría al nivel de América Latina, con las tasas de resistencia más altas.…”
Section: Discussionunclassified
“…In other studies, it was found that tigecycline had excellent in vitro sensitivity but data reflecting clinical outcome is lacking. 20,23,25 It was also reported that there was increased mortality rate in tigecycline-treated patients than in patients treated by other antibiotics. 20 FDA warned health professionals and their medical care organizations about the increased risk of death when intravenous tigecycline is used.…”
Section: Isolation Of Esbl Positive Organisms In Bihs Generalmentioning
confidence: 98%
“…2,7 ESBL organisms have continued to increase in varieties (more than 400 variants detected) 8 and prevalence and are now a global health concern. 4,9,10 The ESBL organisms have implications for clinicians and patients because these are associated with treatment failure, increased morbidity and mortality, poor outcomes, increased length of stay (LOS) in hospital and health care costs. 9 So, it is important to treat it properly as soon as it is diagnosed.…”
Section: Frequency and Sensitivity Of Extended Spectrum Beta-lactamasmentioning
confidence: 99%
See 2 more Smart Citations